2002
DOI: 10.1007/bf02294994
|View full text |Cite
|
Sign up to set email alerts
|

Influence analysis of ranking data

Abstract: ranking data, partition maximum likelihood estimation, local influence, diagnostic measure,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…An influence analysis procedure of ranking data has been developed by Poon and Chan (2002). The building‐blocks of their influence measures are by‐products of the partition maximum likelihood estimation approach of Chan and Bentler (1998), and the measures are developed based on the method of Cook (1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An influence analysis procedure of ranking data has been developed by Poon and Chan (2002). The building‐blocks of their influence measures are by‐products of the partition maximum likelihood estimation approach of Chan and Bentler (1998), and the measures are developed based on the method of Cook (1986).…”
Section: Discussionmentioning
confidence: 99%
“…Various perturbation schemes can be introduced to perturb a model under different contexts to obtain a comprehensive picture of an analysis. For ranking data, the observations are the frequencies of the n 0 distinct response patterns, and a common area of interest is to identify the influential response patterns through the minor perturbation of the frequencies of the patterns (Poon & Chan, 2002). For the factor analysis model, however, the perturbation of the parameters enables the identification of the parameters to which the model is sensitive (Lee & Wang, 1996; Poon et al , 1999).…”
Section: Local Influence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The issues of leniency and central tendency are well known in psychology: it is often observed that individuals have a tendency to place objects in the middle of the scale and to avoid extreme positions. Similar problems have also been studied by Poon and Chan (2002), Fligner and Verducci (1990), and Yu (2000). The mathematics of these methods has been described by Alvo and Yu (2014), Marden (1995), andCritchlow et al (1991).…”
Section: Introductionmentioning
confidence: 93%
“…Typical examples are the applications to nonlinear mixed-effects models (Lee & Xu, 2004), growth curve models (Pan, Fang, & Liski, 1996), and principal component analysis (Shi, 1997), among others. At the same time, the local influence approach of Cook (1986) has also received a lot of attention in factor analysis or structural equation models (SEMs); see, for example, Tanaka and Odaka (1989), Lee and Wang (1996), Kwan and Fung (1998), Poon, Wang, and Lee (1999), Poon and Chan (2002), and Lee and Xu (2003a,b), and Song and Lee (2004a,b). However, as far as we know no local influence analysis for NSEMs has been developed, and it is very difficult to apply Cook's (1986) approach because the building blocks in its diagnostic measures involve intractable integrals that are induced by the nonlinearity among latent variables.…”
Section: Introductionmentioning
confidence: 99%